Стратегічні перспективи розвитку літієвого виробництва в Україні - Логвіненко, Б.І. (Економіка промисловості, 2024)
У сучасному науковому середовищі питання дослідження та використання літію залишається актуальним і привертає увагу багатьох учених по всьому світу. Незважаючи на зміни в глобальних трендах, кожні два-три роки спостерігається повернення науковців до тематики, пов’язаної з літієм, що зумовлено її високою значущістю.
Україна, маючи значні запаси літієвих руд, виступає важливим об’єктом для наукових досліджень у цій сфері. Однак в інформаційному просторі існує значна кількість суперечливих даних щодо наявності, обсягів та якості українських літієвих ресурсів. Це підкреслює необхідність наукового аналізу для отримання достовірної інформації та оцінювання реальних перспектив розвитку літієвої галузі в Україні.
Мета статті ‒ проаналізувати сучасні можливості та виклики, пов’язані з літієвою сферою України, а саме останні дані про запаси літію, перспективи його видобутку та переробки.
Запропоновано проєкт співпраці з корпорацією Tesla, який згідно з виконаними розрахунками може мати щорічний економічний ефект у вигляді впливу на ВВП України, який становитиме приблизно 1,6-1,8% (з урахуванням податкових надходжень та інших інвестицій від реалізації проєкту). Це відкриває нові можливості для розвитку індустрії та сприяє енергетичній незалежності й економічному зростанню країни.
На сьогоднішній день енергетична система України перебуває в критичному стані через постійні обстріли з боку РФ, що підкреслює важливість розвитку власних ресурсів і технологій для забезпечення енергетичної незалежності країни. У даному контексті дослід-ження та розвиток літієвої індустрії набувають особливої значущості.
Систематизовано й узагальнено дані про літієві ресурси України, визначено основні проблеми, а також перспективні напрями розвитку цієї галузі. Проаналізовано сучасні можливості та виклики для літієвої сфери України. Розглянуто перспективи видобутку та переробки літію; запропоновано проєкти розвитку цієї стратегічно важливої галузі. In the modern scientific community, the study and use of lithium remain relevant and attract the attention of many researchers worldwide. Despite shifts in global trends, researchers consistently return to topics related to lithium every two to three years. This is due to the ongoing significance of these issues and the unchanging international interest in them.
In turn, Ukraine, with its significant reserves of lithium ores, serves as an important subject for scientific research in this field. However, there is a considerable amount of conflicting data in the information landscape regarding the availability, volumes, and quality of Ukrainian lithium resources. This highlights the necessity for in-depth and systematic scientific analysis to obtain reliable information and assess the real prospects for the development of the lithium industry in Ukraine.
This scientific work aims to examine the contemporary opportunities and challenges associated with Ukraine’s lithium sector. Specifically, it will analyze the latest data on lithium reserves, consider the prospects for its extraction and processing, and propose projects for the development of this strategically important industry.
A project of cooperation with Tesla was proposed, and calculations showed that this project could have a significant economic impact. It is expected that the annual impact on Ukraine's GDP will be approximately 1.6-1.8%, taking into account tax revenues and other investments from the project. This opens up new opportunities for the development of the industry, will contribute to energy independence and economic growth of the country.
Currently, Ukraine’s energy system is in a critical condition due to constant bombardments by the Russian Federation, which further emphasizes the importance of developing domestic resources and technologies to ensure the country’s energy independence. In this context, the research and development of the lithium industry gain particular significance.
This article attempts to collect, systematize, and analyze available information about Ukraine’s lithium resources, identify the main problems and challenges, and outline prospective directions for the development of this sector. A detailed analysis of the current opportunities and challenges for Ukraine’s lithium sphere has been conducted. The latest data on lithium reserves have been reviewed, the prospects for its extraction and processing have been considered, and several projects for the development of this strategically important industry have been proposed.